2021
DOI: 10.1111/codi.15544
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term gastrointestinal sequelae in colon cancer survivors: prospective pilot study on identification, the need for clinical evaluation and effects of treatment

Abstract: Aim The aim of the present pilot study was to describe the type and frequency of long‐term gastrointestinal symptoms within a well‐defined cohort of colon cancer survivors, their wish for clinical evaluation and treatment outcomes. Method A screening survey was sent to colon cancer survivors 12, 24 and 36 months after surgery. Based on their main symptoms, patients who wished to have a consultation were referred to the gastroenterological or surgical unit of our late cancer sequelae clinic. Treatment effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This improvement is seen not only in the Western world but also in other geographical areas where high-quality care is available [2]. A growing number of CRC survivors suffer from a broad spectrum of late sequelae, including bowel, urinary, sexual dysfunction, fatigue, psychological distress, insomnia, and pain, all of which may severely affect the quality of life (QoL) [3][4][5][6][7][8][9]. Severe persistent postsurgical pain is a…”
mentioning
confidence: 99%
“…This improvement is seen not only in the Western world but also in other geographical areas where high-quality care is available [2]. A growing number of CRC survivors suffer from a broad spectrum of late sequelae, including bowel, urinary, sexual dysfunction, fatigue, psychological distress, insomnia, and pain, all of which may severely affect the quality of life (QoL) [3][4][5][6][7][8][9]. Severe persistent postsurgical pain is a…”
mentioning
confidence: 99%
“…Larsen et al . have shown that when asked in a survey, 10 per cent of Danish colonic cancer survivors have bowel dysfunction and are interested in clinical evaluation and treatment 47 . If cancer survivors with long-term bowel sequelae are identified, evaluated, and treated, there is a potential for helping a large patient group, including those with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients referred for treatment, 56.8% were women with a right-sided hemicolectomy. Among these, 54% had loose stools and 62% were faecally incontinent [58] In a previous study, all of 14 patients with chronic diarrhoea and previous caecal cancer were diagnosed with BAM (SeHCAT < 15%)…”
Section: Bowel Dysfunction After Right-sided Hemicolectomymentioning
confidence: 91%